Forecasting Foreign Tourists to West Sumatera Before and After COVID-19 Using ARIMA and Prophet and Its Impact on Foreign Exchange - Cindy Resha Alandra; Dony Permana; Dodi Vionanda; Dina Fitria (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2025)
Foreign exchange earnings are very important for the improvement of the economy in Indonesia, where these foreign exchange earnings can be obtained through the tourism sector. One of the provinces in Indonesia that is a major tourist destination is West Sumatra. The number of foreign tourists coming to West Sumatra is influenced by various factors, one of which is the COVID-19 pandemic that resulted in a decrease in visitor numbers. The research was conducted to forecast the number of foreign tourists to West Sumatra using the ARIMA and Prophet methods, as well as to calculate the loss and foreign exchange earnings and the forecasting accuracy of both methods. The data for this study was taken from the BPS West Sumatra website regarding the number of foreign tourists to West Sumatra from 2015 to 2024. In this data, forecasting for the year 2020 will be done using the ARIMA method and forecasting for the year 2025 using the Prophet method. The data in this study tends to be stable before the pandemic, making the ARIMA method suitable. Meanwhile, after the pandemic, the data fluctuated, making the Prophet method suitable. From the results obtained, the best ARIMA model is ARIMA (1, 0, 1). The forecasting accuracy is 1.82% with an estimated foreign exchange loss of 52,095,688 for the year 2020. Meanwhile, using the Prophet method, the forecasting accuracy obtained is 12.13% with an estimated foreign exchange revenue of 208,546,812 for the year 2025.